2020
DOI: 10.1108/jefas-05-2019-0069
|View full text |Cite
|
Sign up to set email alerts
|

External debt and growth: role of stable macroeconomic policies

Abstract: Purpose This study aims to examine the impact of external debt on economic growth in Bangladesh within a broader macroeconomic scenario. Design/methodology/approach In the process of doing so, it assesses the empirical cointegration, long-run and short-run dynamics of the concerned variables for the period of 1980–2017 applying the autoregressive distributed lag (ARDL) bounds testing approach to cointegration. First, debt-gross domestic product linkage explores the impact of external debt impact on economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…It is thus necessary to have good foreign debt management that ensures the debt funds are suitably channeled into economic value-added sectors and optimally utilized in order to positively influence growth performance. The situation with foreign debt in Indonesia is also consistent with the research of Hassan and Meyer (2020) and Awad (2020) in Sub-Saharan African (SSA) countries, Dey and Tareque (2019) in Bangladesh, and Ibrahim (2020) in 20 developing countries. However, according to Sajjad et al (2018) the results of ADF testing during the period 1980-2016 in Pakistan, found that external debt was detrimental and statistically significant to GDP growth rate.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It is thus necessary to have good foreign debt management that ensures the debt funds are suitably channeled into economic value-added sectors and optimally utilized in order to positively influence growth performance. The situation with foreign debt in Indonesia is also consistent with the research of Hassan and Meyer (2020) and Awad (2020) in Sub-Saharan African (SSA) countries, Dey and Tareque (2019) in Bangladesh, and Ibrahim (2020) in 20 developing countries. However, according to Sajjad et al (2018) the results of ADF testing during the period 1980-2016 in Pakistan, found that external debt was detrimental and statistically significant to GDP growth rate.…”
Section: Resultssupporting
confidence: 84%
“…At a certain threshold, it will suppress economic growth. This finding is relevant to the research of Dey and Tareque (2019), using autoregressive distributed lag (ARDL) for cointegration, it was found that the negative impact of foreign debt on the growth of Gross Domestic Product in Bangladesh. This can be reduced by proper human resource policies.…”
Section: Literature Reviewmentioning
confidence: 63%
“…Contrariwise, neo-classical economists equate debt to a future tax and focus on the adverse effects of debt overload. Their view is corroborated by another strand of literature which suggests that external debt negatively affects economic growth (Ali and Mustafa 2012;Ciftcioglu and Sokhanvar 2018;Dey and Tareque 2019;Edo et al 2020;Elbadawi et al 1997;Karagol 2002;Soydan and Bedir 2015;Were 2001). Recently, however, attention has shifted towards investigating the non-linear effect of external debt on economic growth.…”
Section: Introductionmentioning
confidence: 82%
“…Rajpurohit and Sharma (2021) observed that moderate economic growth and moderate financial development increase carbon emissions, whereas exponential growth and financial development decrease carbon emissions. Dey and Tareque (2020) observed a negative impact of external debt on GDP growth. Shabbir et al (2020) examined the role of natural resources in economic growth for Pakistan during 1972–2016.…”
Section: Literature Reviewmentioning
confidence: 99%